PERSISTENT ELEVATION OF NEUTROPHIL/LYMPHOCYTE RATIO ASSOCIATED WITH NEW ONSET ATRIAL FIBRILLATION FOLLOWING PERCUTANEOUS CORONARY INTERVENTION FOR ACUTE ST SEGMENT ELEVATION MYOCARDIAL INFARCTION - Chavarria, Nelson; Wong, Cyrus; Hussain, Hafiz; Jooiya, Habib ullah; Goldbarg, Seth; Buda, Andrew (Journal of Ayub Medical College Abbottabad, 2015)
Background: Increasing evidence suggests that inflammation plays an important role in initiation and maintaining of atrial fibrillation (AF). The Neutrophil to Lymphocyte (N/L) Ratio is an easily derived and readily available parameter that has emerged as marker of inflammation with predictive and prognostic value. We investigated the association between N/L ratio and incidence of atrial fibrillation in patients undergoing cardiac catheterization for acute ST-segment elevation myocardial infarction (STEMI). Methods: This cross sectional descriptive study was carried out at New York Hospital Queens. We retrospectively analysed clinical, hematologic and angiographic data of 290 patients who underwent coronary angiography with stent placement for acute ST-segment elevation myocardial infarction between 2008-2011. Results: Study cohort of 290 patients had mean age 63.3±13.0 years consisting of 81.4% male. The N/L ratio was measured at time points: <6 hours pre-catheterization, <12, 48 and 96 hours post catheterization. Patients who developed AF (n=40, 13.8%), had higher post catheterization N/L ratios at 48hours (median 5.23 vs 3.00, p=0.05) and 96 hours (median 4.67 vs 3.56, p=0.03), with no differences in the immediate pre and post procedural measurements, <6 hours pre catheterization (median 2.49 vs 2.82, p=0.467) and <12 hours post catheterization (median 5.93 vs 5.03, p=0.741) respectively. Conclusion: In conclusion, these findings support an inflammatory aetiology contributing to new onset AF following percutaneous coronary intervention for acute STEMI. Further studies are warranted to elucidate these findings. Keywords: Neutrophil/Lymphocyte ratio, Atrial Fibrillation Coronary Angiography, Myocardial Infarction